Biomarkers of Cellular Senescence and Skin Aging - Wang, Audrey S.; Dreesen, Oliver (Frontiers in Genetics, 2018)
Cellular senescence is an irreversible growth arrest that occurs as a result of different damaging stimuli, including DNA damage, telomere shortening and dysfunction or oncogenic stress. Senescent cells exert a pleotropic effect on development, tissue aging and regeneration, inflammation, wound healing and tumor suppression. Strategies to remove senescent cells from aging tissues or preneoplastic lesions can delay tissue dysfunction and lead to increased healthspan. However, a significant hurdle in the aging field has been the identification of a universal biomarker that facilitates the unequivocal detection and quantification of senescent cell types in vitro and in vivo. Mammalian skin is the largest organ of the human body and consists of different cell types and compartments. Skin provides a physical barrier against harmful microbes, toxins and protects us from ultraviolet radiation. Increasing evidence suggests that senescent cells accumulate in chronologically- and photoaged human skin; and may contribute to age-related skin changes and pathologies. Here, we highlight current biomarkers to detect senescent cells and review their utility in the context of skin aging. In particular, we discuss the efficacy of biomarkers to detect senescence within different skin compartments and cell types, and how they may contribute to myriad manifestations of skin aging and age-related skin pathologies.